Management of Secondary Caries in Primary Molars Using Silver Diamine Fluoride: An In-Vitro Study - Osama M Felemban; Arwa A Swead; Deema J Farsi; Sara M. Bagher; Amina M Bagher; Najat Farsi (Wolters Kluwer Medknow Publications, 2024)
Introduction: We aimed to evaluate the effects of 38% silver diamine fluoride (SDF) application on the progression of secondary caries (SC) around resin-based composite (RBC) restoration margins in extracted human primary molars compared to 2.5% fluoride varnish (NaF) with hydroxyapatite and no intervention. Methods: Standardized box-shaped cavities were prepared on 30 primary teeth and restored with RBC restorations. The teeth were thermo-cycled and then immersed in a demineralizing solution for 10 days. The baseline volumes of the demineralized lesions were measured using Micro-CT (first evaluation). Next, the teeth were randomly divided into three equal groups of 10 teeth: the experimental group (38% SDF), the positive control group (2.5% NaF varnish with hydroxyapatite), and the negative control group (no intervention). All teeth were immersed again in the demineralizing solution for 10 days, followed by a second micro-CT evaluation. Results: There was a statistically significant difference in the rate of change of demineralization areas between the three groups (p < 0.001). The SDF group showed the least change in the mean volume of the demineralization area between the baseline and after the second exposure (3.4 ± 0.94 mm3) compared to NaF (4.85 ± 1.97 mm3) and the negative control groups (8.78 ± 2.03 mm3). Conclusion: SDF was effective in managing primary molars with SC around resin-based composite restorations.